Application of Melatonin with N-Acetylcysteine Exceeds Traditional Treatment for Acetaminophen-Induced Hepatotoxicity. (2nd September 2022) - Chen, Mengfei; Ke, Jinfang; Ma, Shilan; Chai, Hua; Zhang, Liang; Zhang, Ling
Abstract : Acetaminophen (APAP) overdose is one of the leading causes of acute liver damage. Given N-acetylcysteine (NAC) and melatonin (MLT) both have an attenuated value for APAP-induced liver toxification, where an optimized integrated treatment has not been well deciphered. Here, by giving a single dose of APAP (500 mg/kg) to wild-type male mice, combined with a single dose of 500 mg/kg NAC or 100 mg/kg MLT separately as the therapeutic method, this study aimed to investigate the effects of NAC and melatonin (MLT) alone or combined on acetaminophen (APAP)-induced liver injury. In this study, NAC and MLT both partially have an alleviated function in APAP-challenged liver injury. However, MLT's add-on role strengthens the hepatoprotective effect of NAC on APAP-induced liver damage and resolute the inflammatory infiltration. Meanwhile, the combination of two reagents attenuates the decreased glutathione (GSH) and activation of the p38/JNK pathway. The combination of MLT and NAC can further ameliorate APAP-induced liver injury, which provides a novel strategy for drug-induced liver injury (DILI).